2016
DOI: 10.1681/asn.2015070772
|View full text |Cite
|
Sign up to set email alerts
|

σ1-Receptor Agonism Protects against Renal Ischemia-Reperfusion Injury

Abstract: Mechanisms of renal ischemia-reperfusion injury remain unresolved, and effective therapies are lacking. We previously showed that dehydroepiandrosterone protects against renal ischemia-reperfusion injury in male rats. Here, we investigated the potential role of σ1-receptor activation in mediating this protection. In rats, pretreatment with either dehydroepiandrosterone or fluvoxamine, a high-affinity σ1-receptor agonist, improved survival, renal function and structure, and the inflammatory response after suble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 46 publications
2
28
0
1
Order By: Relevance
“…Recently, we confirmed the presence of S1R in proximal tubular cells and showed the receptor's translocation upon ligand stimulation . Here we demonstrated that E2 acts directly on S1R and induces the production of heat shock proteins in proximal tubular cells.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Recently, we confirmed the presence of S1R in proximal tubular cells and showed the receptor's translocation upon ligand stimulation . Here we demonstrated that E2 acts directly on S1R and induces the production of heat shock proteins in proximal tubular cells.…”
Section: Discussionsupporting
confidence: 67%
“…All reagents for Western blot were purchased from Bio‐Rad Laboratories (Hercules, CA, USA). Total protein was extracted from kidney cortex and HK‐2 cells as described previously . Protein concentrations were determined in triplicates by Bradford analysis using bovine serum albumin as standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few studies showing the vascular effects of the σ1R modulation (Hosszu et al., ; Tagashira et al., ), although some recent studies showed σ1R expression in vascular tissue (Amer et al., ; Bhuiyan, Tagashira, Shioda, & Fukunaga, ). The repeated administration of MR‐309 was able to correct both the increase in coronary perfusion pressure and endothelial dysfunction in the aorta, which agree with our previous recordings in diabetic rats, demonstrating that MR‐309 treatment can improve vascular parameters (Paniagua et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Several studies demonstrate that sigma-1 receptor stimulation promotes neuroprotection, neuroplasticity, cardioprotection, and renoprotection. [3][4][5] Accordingly, the sigma-1 receptor is a major target of ongoing pharmaceutical research.…”
Section: To the Editormentioning
confidence: 99%